No Sex Differences in Psychological Burden and Health Behaviors of Healthcare Workers During the COVID-19 Stay-at-Home Orders - Gu, Wenli; Liu, Xiao; Sun, Runlu; Jiang, Yuan; Cao, Zhengyu; Wu, Maoxiong; Ma, Jianyong; Chen, Zhiteng; Chen, Yangxin; Zhang, Yuling; Wang, Jingfeng (Frontiers in Medicine, 2021)
Background Females with novel coronavirus disease 2019 (COVID-19) state-ordered home isolation were associated with higher anxiety and reduced sleep quality than males. Sex differences in psychobehavioral changes during the COVID-19 stay-at home orders among healthcare workers remained unclear. The purpose of this study was to explore the sex differences in psychological burden and health behaviors among these persons. Methods This was a cross-sectional study using online data available in the open Interuniversity Consortium for Political and Social Research (OPENICPSR). Healthcare workers including females and males who transitioned to working from home during the COVID-19 stay-at-home orders were included. Sex differences were compared using the chi-square test and Student’s t-test. We performed logistic and linear regression analyses to determine the association of females with psychological burden and health behaviors. Results A total of 537 respondents (425 females and 112 males) were enrolled in our study. Sex differences in age (42.112.3 years vs 46.6 15.7 years, t = -2.821, p = 0.005), occupation (χ2 = 41.037, p < 0.001), mood change (n = 297, 69.9% vs n = 61, 54.5%, χ2 = 9.482, p = 0.002), bedtime schedule (χ2 = 6.254, p = 0.044)) and news consumption (n = 344, 80.9% vs n = 76, 67.9%, χ2 = 8.905, p = 0.003) were statistically significant. Logistic regression showed that females was negatively associated with better mood status (OR=0.586, 95% CI 0.153-2.247, p = 0.436). In addition, linear regression showed that females were not correlated with total sleep time after adjusting for sio-demographics, mental health outcomes and health behaviors (B= 0.038, 95% CI -0.313-0.388, p=0.833). Conclusion No sex differences in psychological burden and health behaviors of healthcare workers were found during the COVID-19 stay-at-home orders. The COVID-19 state-ordered home isolation may be a potential way to reduce disproportionate effects of COVID-19 pandemic on females and help to minimize sex differences in psychological burden and health behaviors among healthcare workers.